2007
DOI: 10.1093/cercor/bhm238
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFI Coordinates Cortical Patterning, Neurogenesis, and Laminar Fate and Modulates MAPK/ERK, AKT, and ß-Catenin Signaling

Abstract: A major unsolved question in cortical development is how proliferation, neurogenesis, regional growth, regional identity, and laminar fate specification are coordinated. Here we provide evidence, using loss-of-function and gain-of-function manipulations, that the COUP-TFI orphan nuclear receptor promotes ventral cortical fate, promotes cell cycle exit and neural differentiation, regulates the balance of early- and late-born neurons, and regulates the balanced production of different types of layer V cortical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(163 citation statements)
references
References 95 publications
7
154
2
Order By: Relevance
“…In the present study, we provide evidence that COUP-TFI is an upstream negative regulator of a CSMN differentiation program in corticofugal neurons, through repression of a genetic program of CSMN differentiation. First, during the period of corticofugal neuron birth and specification, an increased number of Fezf2-and CTIP2-positive neurons in COUP-TFI CKO mice are generated; second, COUP-TFI-deficient neurons in layers V and VI express abnormally high levels of Fezf2, CTIP2, Crim1, and Igfbp4; third, gain-of-function of COUP-TFI in a transgenic model shows decreased expression of Fezf2 and other layer V markers (19). An especially interesting aspect of these results is the abnormal differentiation of genuine CSMN in layer V of COUP-TFI CKO mice, including failure of these neurons to send projections to the spinal cord.…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we provide evidence that COUP-TFI is an upstream negative regulator of a CSMN differentiation program in corticofugal neurons, through repression of a genetic program of CSMN differentiation. First, during the period of corticofugal neuron birth and specification, an increased number of Fezf2-and CTIP2-positive neurons in COUP-TFI CKO mice are generated; second, COUP-TFI-deficient neurons in layers V and VI express abnormally high levels of Fezf2, CTIP2, Crim1, and Igfbp4; third, gain-of-function of COUP-TFI in a transgenic model shows decreased expression of Fezf2 and other layer V markers (19). An especially interesting aspect of these results is the abnormal differentiation of genuine CSMN in layer V of COUP-TFI CKO mice, including failure of these neurons to send projections to the spinal cord.…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentmentioning
confidence: 99%
“…Using cortexspecific conditional loss-of-function of COUP-TFI, we have previously demonstrated that this transcription factor is critical for areal patterning by acting in sensory cortex to repress frontal/motor cortical area identity (17). COUP-TFI has also been shown to regulate neuronal differentiation (19) and, together with COUP-TFII, to control the timing of the switch of progenitor cells from neurogenesis to gliogenesis in the developing cortex (20). Given the dual function of COUP-TFI in neuronal and areal specification, we hypothesized that COUP-TFI might control sensory area formation by repressing a "motorizing" genetic program of differentiation in neurons of the somatosensory cortex.…”
mentioning
confidence: 99%
“…3B). The roles of COUP-TFI in cortical development have been studied in germline and cortexspecific mutant mice, and have also been investigated by in vivo overexpression (Zhou et al 2001;Armentano et al 2007;Faedo et al 2008). In mice with a cortex-specific deletion of COUP-TFI, the expression of regional cortical plate markers Cdh8, Id2, Fezf2, and Efna5 revealed that the balance of area pattern was changed such that the majority of the cortex was transformed into motor cortex, and the somatosensory and visual areas were greatly reduced in size and located at the caudal pole of the structure (Fig.…”
Section: Fgf Signaling Establishes An Opposing Gradient Of the Caudalmentioning
confidence: 99%
“…The regulation of FGF signaling by COUP-TFI is less well understood. However, reduced levels of phospho-Erk1/2 have been reported in the neocortex of mice constitutively overexpressing COUP-TFI, indicating that COUP-TFI can negatively regulate FGF signaling (Faedo et al 2008). The ability of FGF to repress the expression of COUP-TFI indicates that the Fgf-signaling gradient is responsible for establishing the caudal-high to rostral-low gradient of COUP-TFI in the neocortex, in a manner analogous to that of the repression of dorsally expressed class II transcription factors in the spinal cord by the ventrally secreted morphogen sonic hedgehog (Briscoe and Ericson 2001).…”
Section: Fgf Signaling Establishes An Opposing Gradient Of the Caudalmentioning
confidence: 99%
“…Recently, it has been reported that the canonical Wnt pathway is also important for cellular proliferation in the ventricular zone and for fate determination in the cortex (Chenn and Walsh, 2002;Backman et al, 2005;Zhou et al, 2006;Woodhead et al, 2006;Machon et al, 2007). Furthermore, it was recently shown that neurogenesis in the cortex is directly correlated with a gradual decrease of canonical Wnt signaling (Machon et al, 2007;Faedo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%